1986
DOI: 10.1056/nejm198608143150703
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arteriographic Findings Soon after Non-Q-Wave Myocardial Infarction

Abstract: Complete occlusion of the infarct-related coronary artery is a frequent finding soon after Q-wave (transmural) myocardial infarction. We performed coronary arteriography to study the frequency of total coronary occlusion and of angiographically visible collateral vessels in 341 patients within one week of non-Q-wave myocardial infarction. In this cross-sectional study, 192, 94, and 55 patients underwent coronary arteriography within 24 hours of peak symptoms, between 24 and 72 hours after peak symptoms, and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
107
1
7

Year Published

1987
1987
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 412 publications
(118 citation statements)
references
References 35 publications
3
107
1
7
Order By: Relevance
“…Many studies have reported that the pathophysiologic mechanisms involved in non-Q wave myocardial infarction differ from those in Q wave infarction, with less frequent coronary artery thrombosis'' 42 and less extensive injury but a higher propensity for postinfarction angina and reinfarction in patients with the former.`' Thus, despite an initial favorable prognosis, long-term survival after non-Q wave myocardial infarction is similar to, or even less favorable, than that after Q wave infarction.7'9 43' A previous history of angina pectoris or of myocardial infarction has also been shown to be associated with more extensive coronary artery disease and with a poor prognosis.4 18 45 When only the clinical characteristics were entered in the logistic regression, the number of risk factors also became an independent predictor. Combining the three clinical characteristics it was possible 24 hr after admission to accurately predict subgroups at high, medium, and low risk of occurrence of early ischemia (figure 1), with a non-Q wave myocardial infarction being one of the major determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the pathophysiologic mechanisms involved in non-Q wave myocardial infarction differ from those in Q wave infarction, with less frequent coronary artery thrombosis'' 42 and less extensive injury but a higher propensity for postinfarction angina and reinfarction in patients with the former.`' Thus, despite an initial favorable prognosis, long-term survival after non-Q wave myocardial infarction is similar to, or even less favorable, than that after Q wave infarction.7'9 43' A previous history of angina pectoris or of myocardial infarction has also been shown to be associated with more extensive coronary artery disease and with a poor prognosis.4 18 45 When only the clinical characteristics were entered in the logistic regression, the number of risk factors also became an independent predictor. Combining the three clinical characteristics it was possible 24 hr after admission to accurately predict subgroups at high, medium, and low risk of occurrence of early ischemia (figure 1), with a non-Q wave myocardial infarction being one of the major determinants.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary angiography within 24 hours of pain onset revealed an open infarct artery in 74% (143 of 192) of patients with non-Q-wave infarction 50 compared with only 19% (98 of 517) in those with Q-wave myocardial infarction. 51 Collateral flow to the totally occluded infarct artery was present in 86% (42 of 49) of patients with non-Q-wave infarction 50 but in only 33% (66 of 199) of patients with predominantly Q-wave infarction.…”
Section: Q-wave Versus Non-q-wave Myocardial Infarctionmentioning
confidence: 96%
“…51 Collateral flow to the totally occluded infarct artery was present in 86% (42 of 49) of patients with non-Q-wave infarction 50 but in only 33% (66 of 199) of patients with predominantly Q-wave infarction. 52 Non-Q-wave infarcts differed from Q-wave infarcts by earlier creatine phosphokinase peaks and smaller infarct size as assessed by left ventricular function parameters, thallium scintigraphy, and enzyme release.…”
Section: Q-wave Versus Non-q-wave Myocardial Infarctionmentioning
confidence: 97%
“…Angiographic studies showed that luminal obstructions by thrombus in culprit coronary arteries are significantly different according to the presence of ST segment elevation. Acute STEMI is most commonly caused by acute total thrombotic occlusion of a coronary artery, whereas USAP/NSTEMI is usually associated with severe coronary obstruction but no total occlusion of the culprit coronary artery [12][13][14][15]. The question why the thrombus occludes the culprit artery totally in some patients and not totally in others is not clearly answered.…”
Section: Discussionmentioning
confidence: 99%